Enhancing text-level reading fluency and engagement in immigrant children through a structured singing-based intervention - Choe, Eunjin; Lee, Mihye; Kim, Soo Ji (Frontiers in Psychology, 2025)
IntroductionReading fluency is a key component of academic success, yet immigrant children often face difficulties in developing this skill in a new language due to limited phonological awareness, reduced exposure, and differences between home and school language environments. This pilot study examined the effects of a singing-based intervention designed to improve reading fluency and attitudes toward reading among immigrant children.MethodsEight elementary school children from immigrant backgrounds participated in an eight-session program conducted twice weekly for 50 minutes per session. The intervention integrated rhythm-based word chanting, sentence singing, and songwriting. Pre- and post-intervention assessments included the Reading Fluency Test measuring accuracy, automaticity, and prosody, and a modified Reading Attitude Inventory assessing interest, habits, and perceptions. Semi-structured interviews were also conducted to explore participants’ experiences and perceived changes.ResultsQuantitative analyses indicated overall improvements in reading fluency, particularly in accuracy and automaticity. Participants also reported increased reading interest and more positive literacy attitudes. Children with longer residence in Korea showed greater gains, though progress was also observed among those with limited exposure.DiscussionFindings provide preliminary evidence that singing-based interventions may enhance reading fluency and engagement among immigrant children. The rhythmic and melodic features of singing may support phonological and prosodic processing that underlie fluent reading. However, the small sample size, brief duration, and absence of standardized comprehension measures highlight the need for larger, longitudinal studies.